Hubungan Sarapan Pagi Dengan Kejadian Anemia Di SMP Negri 3 Perhentian Raja Kabupaten Kampar Tahun 2023 - Syafira, Adella; Harahap, Dewi Anggriani; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Teenagers need nutrients that function as a source of energy and play a role in body metabolism, including the formation of hemoglobin. Nutrient intake will be reduced by 30% if someone skips breakfast and this directly reduces hemoglobin production, causing anemia. The aim of this research was to determine the relationship between breakfast and the incidence of anemia in adolescent girls at SMP Negeri 3 Perhentian Raja, Kampar Regency in 2023. This type of research is quantitative, analytical in nature with a cross sectional design. The population in this study was the total number of young women at SMP Negeri 3 Perhentian Raja, namely 112 young women. The sample in this study used total sampling, where the number of samples is the same as the population. The data collection tools in this research are questionnaires and digital HB. Then the data was analyzed Univariately and Bivariately using the Chi-Square test. The research results showed that there was a relationship between breakfast and the incidence of anemia with a p value of (0.002). The conclusion is that there is a significant relationship between breakfast and the incidence of anemia in adolescent girls at SMP Negeri 3 Perhentian Raja, Kampar Regency in 2023